Balancing support and bureaucracy: the enabling–constraining dynamics of research funding policies in a Philippine state university - John Michael D. Aquino; Rushid Jay S. Sancon (Institute of Advanced Engineering and Science, 2026)
Research funding policies has a critical role in shaping research productivity and governance in higher education institutions (HEIs). However, limited empirical studies have examined how these policies are experienced by faculty members and administrators, particularly in state universities within developing country contexts. This study explores the implementation of research funding and assistance guidelines in a Philippine state university using a phenomenological approach. Data were collected from 34 participants (15 administrators and 19 faculty members) through semi-structured interviews and document analysis and were analyzed thematically. The findings reveal an enabling–constraining dynamic in the implementation of research funding policies. Institutional support, including funding, incentives, and structured processes, enhances faculty motivation, research engagement, and planning quality. Conversely, bureaucratic complexity, procedural rigidity, and delays in fund release constrain efficiency, limit participation, and discourage sustained engagement. Anchored in self-determination theory (SDT) and structuration theory, the study demonstrates how research funding policies simultaneously influence faculty motivation and are shaped by institutional structures. These findings highlight the need for streamlined processes, consistent implementation, and faculty-centered support systems. The study contributes to the literature by providing empirical evidence of the enabling–constraining paradox of research funding policies and offers insights for improving research governance in higher education.